Rules for Numerals in Hebrew and their Correspondence with Arabic Rules - Vahid Safiyya (دراسات في اللغة العربيّة وآدابها)
Hebrew and Arabic belong to the family of Semitic languages. This means that it is easy to show the similarities between the two languages, particularly in terms of grammatical rules. Original Hebrew texts state that Jews could author texts on the rules of their language only after going through a period of apprenticeship with Arab. They followed the Arab syntacticians in formulating Hebrew grammar rules. Hence, comparative study of the language rules of the two languages can shed light on the obscure areas and help remove many problems, some of which are impossible to solve other than by using comparative methods. Similarly, comparative study help Arabs keen on learning Hebrew and makes its learning easier for them.